(untitled) (Bangladesh Medical Journal, 2019)
A 65-year old Bangladeshi woman with Systemic Lupus Erythematosus (SLE) developed Parkinson-like movement disorder. Steroid pulse therapy followed by prednisolone was most effective in this case. Psychosis, seizure and meningitis are common central nervous system (CNS) manifestations in SLE patients, and Parkinson-like rigidity or tremors are rare. Bangladesh Med J. 2019 Jan; 48 (1): 50-53